Does the commercial real estate industry need "more pussy on the block?". Issue 5 (30th July 2019) - Read, Dustin C.
Abstract : Purpose: In a controversial 2018 interview, commercial real estate mogul Sam Zell insinuated that companies should promote their employees based exclusively on merit and avoid purposefully taking steps to get "more pussy on the block" in the name of gender equality. The comment was criticized not only for its crassness, but also for its failure to recognize the challenges many women working in the commercial real estate industry face in their efforts to obtain the same opportunities, compensation and status as similarly-qualified men. In an effort to overcome these disparities, the purpose of this paper is to focus on the pervasiveness of second-generation gender bias and stereotyping in the field through a qualitative analysis. Design/methodology/approach: Semi-structured interviews were conducted with 39 women serving as local chapter presidents of a prominent commercial real estate trade group to explore the impact of gender on their career advancement and their experiences with second-generation gender bias. Findings: The findings suggest unintentional discrimination often influences women's careers by drawing their communication skills, professional credibility and commitment to the organizations for whom they work into question. Originality/value: The research contributes to the existing literature by offering additional evidence that unintentional discrimination is common in male-dominated industries, such as commercial real estate. It also provides clear examples of social cues women perceive to heighten tension along gender lines and impinge upon their ability to ascend to leadership positions.